Timing the deposition of (17)O-depleted barite at the aftermath of Nantuo glacial meltdown in South China - Zhou, Chuanming (周传明); Bao, Huiming (鲍惠铭); Peng, Yongbo (彭永波); Yuan, Xunlai (袁训来) (Geology, 2010)
Barite in basal Ediacaran cap carbonates in South China shows distinct, non-mass-dependent depletion in O-17, a signal most likely reflecting an extremely high pCO(2) atmosphere during Marinoan glacial meltdown. The precise geological context of the barite within the cap carbonate was not defined, however, and such information is crucial to an accurate interpretation of the anomalous O-17 signal. Based on an extensive field survey of Marinoan cap carbonates in South China and detailed sedimentological, petrographic, and isotope data, we propose here a unified sequence of events that followed the deposition of the Nantuo diamictite: the cap dolostone was first deposited and later uplifted due to isostatic rebound, undergoing karstic dissolution in both shallow platform and transitional facies of the Yangtze Block; subsequent transgression initiated a consistent sequence of mineral deposition on karstic surfaces or within cavities. The O-17-depleted barite, either visible on outcrops or identifiable in thin sections, is among the first minerals precipitated when the transgression flooded the karstified cap dolostone. The calcite with extremely negative delta C-13 values occurs at the last stage of the cavity filling, well after the deposition of cap dolostone and the O-17-depleted barite, suggesting that the signal of methane hydrate was registered much later in the cap dolostone. A similar recognition of karstic dissolution and subsequent barite deposits in cap dolostones in northwest Africa and northwest Canada suggest that deposition of the O-17-depleted barites may be a global event, recording an atmospheric-biological-hydrological condition shortly (within 0-1.6 m.y.) after the initial meltdown of the Marinoan snowball Earth.